Compressive Strength and Hydration of Ravennagrass Baggase Ash Concrete - Elkaseem, Ashhabu; Bawa, Samaila (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
The paper presents the findings of the effect of revennagrass baggase ash concrete compressive strength using compression machine and hydration behavior with the aid of non-contact electrical resistivity measurement device. The result indicates that concrete containing 20% of Revennagrass Baggase Ash recorded the highest compressive strength for 1day, 3days, 7days and 28days respectively. This indicates that, the higher the increase in baggase ash the more the concrete strength up to 20% as the maximum dosage. The reverse is the case in terms of setting time, where the increase in the percentage addition brings about delay in setting time of concrete.